Queue time analysis for a production line with small variability - Wong, Lisa Ley Yien (2017)
Much effort has been put into computing queue times for tandem queue networks as they form a paramount structure of the queuing network. However, it is highly challenging and time consuming to determine the exact queue times. Researchers have proposed several approximation methods for estimating the mean queue times for single server tandem queues. Of which, one involved the exploitation of its Intrin- sic Ratio. This article proposes an approximation approach for homogeneous server two-staged tandem queues by incorporating this approximation method. Using the simulation results obtained for different cases, while varying number of servers in each stage, service time, sample size etc, behavior of the queue networks were stud- ied by observing its intrinsic ratio and intrinsic gap. This study aims to establish a homogeneous trend between intrinsic ratio and traffic intensity, by observing how the intrinsic ratio varies of traffic intensity for each queue setting. Wu and McGinnis (2012) determined that intrinsic ratios are relatively constant as utilization increases for single server tandem queues with squared coefficient of variance less than one. Therefore, this paper also aims to determine if such properties also apply to tandem queues with homogeneous servers. Using the trends identified, backed with mathe- matical formulas, an accurate approximation of queue time can be determined.